Bertahan di Masa Pandemi: Pendekatan Mengajar Guru di Daerah Terpencil - Ridwan Yusuf Deluma; Nelfi Nelfi; Nasir Nasir; Apriani Safitri; Ishak Bagea (Journal of Education and Teaching (JET), 2023)
The corona virus (covid 19) has caused a shift in the educational landscape from in-person instruction to distance learning, which necessitates a digital transformation. For learning to continue to function successfully, teachers must be adept at selecting and implementing the appropriate strategy. The purpose of this study was to learn how teachers in junior high schools in rural areas approached their lessons during the Covid 19 outbreak. This study employs a descriptive qualitative methodology. Three school principals and 108 teachers served as the informants (interview subjects). In addition, a questionnaire was utilized by the researchers to collect information on the teacher's name, age, school's location, previous educational level, gender, and the learning tactics and resources she or he employed during the pandemic. The process of interasis analysis was employed during the data analysis, and it included data reduction, data presentation, and verification or conclusion. According to the study's findings, teachers in remote locations use offline, online, and hybrid teaching methods. Researchers also discovered that the learning strategy employed depends on the teacher's age.